Haemodynamic stroke and transient ischaemic attack secondary to neurocardiovascular instability - Ryan, Daniel J. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Medical Gerontology, 2014)
Introduction: Presyncope or syncope are regarded as benign conditions. In patients with severe large artery disease, hypotension may potentiate infarction, specifically in low-flow vulnerable, borderzone regions of the brain. However, borderzone infarction accounts for 12.5% of infarcts. Thus it is more common than the attributed cuase. This thesis investigated the possibility that presyncope or syncope may potentiate borderzone infarction in the absence of severe large artery stenosis, highlighting the hazardous effects of hypotension.
Keywords: Gerontology, Ph.D.; Ph.D. Trinity College Dublin